Polystyrene nanoparticles: the mechanism of their genotoxicity in human peripheral blood mononuclear cells. Issue 6 (14th September 2022) - Malinowska, Kinga; Bukowska, Bożena; Piwoński, Ireneusz; Foksiński, Marek; Kisielewska, Aneta; Zarakowska, Ewelina; Gackowski, Daniel; Sicińska, Paulina
Abstract: Plastic nanoparticles are widely spread in the biosphere, but health risk associated with their effect on the human organism has not yet been assessed. The purpose of this study was to determine the genotoxic potential of non-functionalized polystyrene nanoparticles (PS-NPs) of different diameters of 29, 44, and 72 nm in human peripheral blood mononuclear cells (PBMCs) ( in vitro ). To select non-cytotoxic concentrations of tested PS-NPs, we analyzed metabolic activity of PBMCs incubated with these particles in concentrations ranging from 0.001 to 1000 µg/mL. Then, PS-NPs were used in concentrations from 0.0001 to 100 μg/mL and incubated with tested cells for 24 h. Physico-chemical properties of PS-NPs in media and suspension were analyzed using dynamic light scattering (DLS), atomic force microscopy (AFM), scanning electron microscopy (SEM) and zeta potential. For the first time, we investigated the mechanism of genotoxic action of PS-NPs based on detection of single/double DNA strand-breaks and 8-oxo-2′-deoxyguanosine (8-oxodG) formation, as well as determination of oxidative modification of purines and pyrimidines and repair efficiency of DNA damage. Obtained results have shown that PS-NPs caused a decrease in PBMCs metabolic activity, increased single/double-strand break formation, oxidized purines and pyrimidines and increased 8oxodG levels. The resulting damage was completely repaired in the case of the largest PS-NPs. It was also found that extent of genotoxic changes in PBMCs depended on the size of tested particles and their ζ-potential value.